2016
DOI: 10.17533/udea.iee.v34n1a20
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of quality of life with the knowledge and attitude of diabetic elderly

Abstract: How to cite this article: Sousa MC, Dias FA, Nascimento JS, Tavares DMS. Correlation of quality of life with the knowledge and attitude of diabetic elderly. Invest Educ Enferm. 2016; 34(1): 180-188. DOI: 10.17533/udea.iee.v34n1a20Correlation of quality of life with the knowledge and attitude of diabetic elderly Objective. To describe the quality of life (QL), knowledge and attitude of the elderly with diabetes mellitus (DM) and to correlate the QL with the knowledge and the attitude of the elderly. Method. It … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
8
1
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 15 publications
5
8
1
4
Order By: Relevance
“…This finding was similar to other studies which also found the highest mean scores in the Social Relationships domain 11,[17][18][19] .…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…This finding was similar to other studies which also found the highest mean scores in the Social Relationships domain 11,[17][18][19] .…”
Section: Discussionsupporting
confidence: 92%
“…In contrast, a lower score was observed in the Environment domain, illustrating the low satisfaction of this population group with the environment in which they live, a result similar to that found in another study with elderly people with DM in Uberaba (Minas Gerais) 7 and with elderly people with DM in the rural part of Bahia 11 . Another study conducted with 277 elderly people in the Distrito Federal also resulted in low QoL scores in the Environment domain, which may be related to the fact that the elderly do not feel safe and protected in their home environment 9 .…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations